Factors associated with renal impairment in Chinese patients with non-valvular AF and without an established renal disease: a cross-sectional study. Issue 5 (3rd July 2020) - Shen, Youmei; Wang, Jing; Chen, Hongwu; Li, Mingfang; Chen, Minglong
ABSTRACT: Background: Renal impairment and atrial fibrillation (AF) often coexist. However, risk factors associated with renal impairment in AF patients have not been studied in a large population. Accordingly, this study investigated clinical factors associated with renal impairment in AF patients. Methods: From January 2012 to December 2016, 2, 298 inpatients with non-valvular AF (NVAF) mainly for catheter ablation were enrolled in this cross-sectional study. Data collection included past medical history, echocardiography measurements, current medicine use and biochemical results. The estimated glomerular filtration rate (eGFR) was calculated using the abbreviated Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI) equation. Renal impairment was defined as a history of chronic kidney disease or an eGFR ≤90 ml/min/1.73 m 2 . Multivariate logistic regression was conducted to evaluate the relationship between the factors screened and eGFR. Results: The mean eGFR was 88.6 ± 17.1 ml/min/1.73 m 2 . The overall prevalence of renal impairment was 47.4%. Multivariate logistic regression showed that factors associated with renal impairment were age (OR: 1.12; 95% CI: 1.11–1.14), non-paroxysmal AF (OR: 1.28; 95% CI: 1.04–1.58), use of angiotensin-converting enzyme inhibitors (ACEI)/angiotensin receptor blockers (ARB) (OR: 1.58; 95% CI: 1.28–1.95), congestive heart failure (OR: 1.80; 95% CI: 1.05–3.07), left ventricular ejection fraction (LVEF) <50% (OR: 2.39; 95% CI: 1.34–4.28), and prior transient ischemic attack (TIA)/stroke/systematic embolism (SE) (OR: 2.69; 95% CI: 1.68–4.29). Conclusions: Renal dysfunction is highly prevalent in Chinese NVAF patients and is significantly associated with older age, non-paroxysmal AF, use of ACEI/ARB, congestive heart failure, LVEF <50% and prior TIA/stroke/SE. Further studies on the mechanisms by which these risk factors affect renal function in NVAF patients need to be conducted.